A Highly Stretchable Fiber‐Based Triboelectric Nanogenerator for Self‐Powered Wearable Electronics. (20th December 2016) - He, Xu; Zi, Yunlong; Guo, Hengyu; Zheng, Haiwu; Xi, Yi; Wu, Changsheng; Wang, Jie; Zhang, Wei; Lu, Canhui; Wang, Zhong Lin
Abstract : The development of flexible and stretchable electronics has attracted intensive attention for their promising applications in next‐generation wearable functional devices. However, these stretchable devices that are made in a conventional planar format have largely hindered their development, especially in highly stretchable conditions. Herein, a novel type of highly stretchable, fiber‐based triboelectric nanogenerator (fiber‐like TENG) for power generation is developed. Owing to the advanced structural designs, including the fiber‐convolving fiber and the stretchable electrodes on elastic silicone rubber fiber, the fiber‐like TENG can be operated at stretching mode with high strains up to 70% and is demonstrated for a broad range of applications such as powering a commercial capacitor, LCD screen, digital watch/calculator, and self‐powered acceleration sensor. This work verifies the promising potential of a novel fiber‐based structure for both power generation and self‐powered sensing. Abstract : A highly stretchable/fiber‐like triboelectric nanogenerator (fiber‐like TENG) is developed with a unique structure for effectively harvesting energy at a range of low frequency stretching motions. By optimizing the device structure, this fiber‐like TENG verifies its promising applications in both power generation for wearable electrics and self‐powered sensing for acceleration rates.